Etnopedagogik qadriyatlardıń tikleniwi – ádep-ikram tárbiyasınıń girewi - Pazılov, A.K (SCIENCE and SOCIETY, 2025)
The article provides a scholarly assessment of the concept of value and provides a comparative analysis of the state and society's approach to national values in the pre-independence period, as well as the current approach to moral education.
Keywords: ethnopedagogy; folk pedagogy; value; human; national value; morality; respect; honor; ancestral heritage